297 ADHERENCE TO DENOSUMAB PRESCRIPTION FOLLOWING DISCHARGE FROM A GERIATRIC REHABILITATION UNIT. (25th October 2022) - Lynch, A; Murray, D; Whelan, O; Mello, S
Abstract: Background: Post-acute geriatric rehabilitation units are an ideal setting to address bone health following acute admission with a fracture. Longer lengths of stay allow for vitamin D replacement and comprehensive multidisciplinary input. However, persistence with osteoporosis medications is suboptimal amongst older Irish adults, and breaks in therapy reduce the medications effectiveness. This study aims to determine adherence rates to Denosumab six-months after discharge from geriatric rehabilitation in patients with fragility fracture who either commenced or continued treatment whilst an inpatient. Methods: Patients admitted with fragility fracture between January and October 2021 were identified through review of an online database. The type of osteoporosis medication, and dates of treatment were documented. Adherence to denosumab prescription six months post-discharge was checked using the Primary Care Reimbursement Service (PCRS) database. Results: 98 patients were admitted with fragility fractures, representing one third of total admissions. Patients were excluded for incomplete data (10), transfer back to acute facility (10) or death (4). Of the 74 included, the average age was 80 (range 65-94), and 53 (71%) female. One in five had a diagnosis of dementia. 52 Patients received first dose Denosumab as an inpatient, 4 were continuing on Denosumab, 11 were on bisphosphonates (4 changed from Denosumab on discharge) and 10 not on bone protection. The majority of patients (N=30, 57%) who had Denosumab administered in hospital did not have the second dose administered at six months. Conclusion: In keeping with prior research, this study found that persistence with osteoporosis medications is low. Reasons are multifactorial and may include the infrequent timing of Denosumab and a lack of reminders to give the medication in primary care settings. New guidelines recommend enhanced screening for and treatment of osteoporosis in frail older adults including follow-up appointments to check adherence to treatment.